Online javno dostopni katalogi in sistemi za odkrivanje informacij - Wells, David N. (Organizacija znanja, 2023)
This article provides an overview of computer-based catalogue systems designed for use by library clients, seeing present day discovery systems on the same trajectory as the older online public access catalogues (OPACs) which they are gradually replacing, both in technical development and their approach to client use scenarios. It traces the history of the OPAC/discovery system from its origins in the library automation of the 1960s through to the present and discusses the main technical standards which have formed its development. The article goes on to consider questions relating to the usability of electronic library catalogues and highlights semiotic and ethical issues inherent to their design. It concludes with reflections on the future of the OPAC/discovery system in an information universe apparently dominated by the Internet search engine.
Keywords: discovery system; knjižnični katalogi; library catalogue; OPAC; sistemi za odkrivanje informacij